A phthalocyanine-based liposomal nanophotosensitizer with highly efficient tumor-targeting and photodynamic activity. (September 2020) - Lin, Ai-Lan; Fan, Ping-Ping; Liu, Shuang-Feng; Chen, Jia-Hui; Zhao, Yuan-Yuan; Zheng, Bi-Yuan; Ke, Mei-Rong; Huang, Jian-Dong
Abstract: Phthalocyanines are promising photosensitizers for photodynamic therapy (PDT), but the inherent tendency of aggregation generally leads to the decrease or even quenching of photoactivities. To address this issue and realize the desirable photodynamic therapeutic effect of phthalocyanines, herein, we report a folate-modified phthalocyanine-based liposomal nanophotosensitizer (PcN@Lip-FA ), which can be prepared through a facile "one-pot" method. An analogue (PcN@Lip ) without folate was also prepared as a negative control. The liposomal nanophotosnesitizers greatly prevented the aggregation of the zinc(II) phthalocyanine (PcN ) and showed highly efficient photoactivities (fluorescence and singlet oxygen generation) in aqueous solutions, although the free PcN is severely aggregated and its photoactivities are nearly quenched. The in vitro results demonstrate that PcN@Lip-FA can be taken in by folate receptor (FR)-positive HeLa cells through FR-mediated process, and exhibits significantly higher cellular uptake and photocytotoxicity against HeLa cells than both PcN@Lip and PcN, but for FR-negative MCF-7 cells, PcN@Lip-FA and PcN@Lip show comparable photocytotoxicity. In addition, with the folate vector, PcN@Lip-FA has highly efficient tumor targeting and PDT effect on the S180 rat ascitic tumor-bearing mice with a tumor inhibition rate up to 98.0%. Therefore, the liposomal nanophotosensitizer PcN@Lip-FA can serve as a promising nanoplatform for cancer diagnosis and targeted PDT. Graphical abstract: Image 1 Highlights: A folate-modified phthalocyanine-based liposomal nanophotosnesitizer was prepared. The liposomal carrier reduced aggregation and enhanced photoactivities of free PcN. PcN@Lip-FA could selectively kill HeLa cells with enhanced photodynamic activity. PcN@Lip-FA had highly efficient tumor targeting and in vivo photodynamic efficacy. Its tumor inhibition rate on the S180 rat ascitic tumor-bearing mice was up to 98.0%.